Methemoglobin and Sulfhemoglobin Levels in Students of Walailak University - TRIAPIRUX, Uthai; NA-EK, Prasit; KITTHIPONGVIVAT, Chinnaphat; CHALAJIT, Surachate (Walailak Journal of Science and Technology (WJST), 2011)
Methemoglobin (MHb) and Sulfhemoglobin (SHb) are abnormal oxygen-carrying protein hemoglobins (Hbs) in blood circulation which can be used to represent the degree of pollution in the surrounding environment including air, food and drinks. The MHb is an oxidized form of hemoglobin (Hb) in which the ferrous ion (Fe2+) in the heme group is oxidized to the ferric ion (Fe3+) by oxidizing agents mostly from the air, food, drinks and drugs. The SHb is a sulfurated form of Hb derived from hydrogen sulfide (H2S) and sulfur dioxide (SO2) gas contained in the air and drugs found in sulfur therapy, respectively. These types of Hb derivatives are unable to bind and carry oxygen to the tissues of the body. This makes inspiration insufficient and may cause cyanosis in increased amounts. The aim of this study is to measure MHb and SHb levels in Walailak University students. EDTA blood samples were collected from 200 students. The MHb and SHb were analyzed by spectrophotometry. The results revealed that the mean MHb and SHb levels of the 200 subjects were 1.29 ± 0.57 % and 0.66 ± 0.28 %, respectively. The level of MHb and SHb in population of Walailak University was very low compared to people in large cities such as Bangkok. The study proves that the environment of Walailak University remains clean, good and fresh.